StASR 2 Overexpression Decreases Salicylic Acid Accumulation Leading to Lower Stomatal Conductance in Nicotiana tabacum - Hanyu, Wu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2018)
Plant ASRs (ABSCISIC ACID STRESS RIPENING ) contains conserved domains in response to ABA and water deficiency, which function on fruit development and drought response. Overexpression of ASR leads to stoma close, enhancing plant tolerance to drought. However, it is unknown yet that how ASR regulates stoma close or open. In this study, morphological and physiological phenotypes were assayed with transgenic lines overexpressing StASR 2 cDNA from potato in Nicotiana tabacum. Data analysis showed that overexpressing StASR 2 resulted in decrease on stoma conductance and transpiration ratio, attributing to a low salicylic acid accumulation level. Although accumulations of chlorophyll and ATP intensified in StASR 2 overexpression lines, net photosynthesis ratio was attenuated owing to reduced stoma conductance. Meanwhile, StASR 2 overexpression leaflets no long appeared sensitivity to ABA treatment and no significant changes on leaf ABA contents was detected between StASR 2 overexpression and control. The result indicates that less salicylic acid accumulation mediates involvement of StASR 2 overexpression in stomatal close rather than ABA.